Notes on Arbitration in the New General Law on Public Procurement - Juárez Guerra, Luis (2025)
This article analyzes several arbitration provisions contained in the new General Law on Public Procurement – Law No. 32069, which, in the author’s view, are controversial, incomplete, or require further development for better understanding.In particular, it examines aspects related to procedural rules applicable to arbitration, substantive rules governing the merits of the case, judicialization of claims arising from the total or partial non-approval of additional services, continuity in the performance of contractual obligations, the statute of limitations in arbitration, the binding nature of the arbitral award, and the countersecurity required for interim measures.